Evidence for a common high affinity binding site on glutathione S-transferase B for lithocholic acid and bilirubin. - Y Sugiyama; A Stolz; M Sugimoto; N Kaplowitz (Journal of Lipid Research, 1984)
Binding of lithocholic acid, bilirubin, and gossypol to glutathione S-transferase B (ligandin or transferase YaYc) was compared using four methods. Tryptophan quenching revealed a single high affinity site for bilirubin and gossypol but could not be used for lithocholic acid. Both displacement of the fluorescent probe, 1-anilino-8-naphthalenesulfonate, and spectral changes induced by bilirubin binding demonstrated a common high affinity site for which all three ligands compete. Similar results were obtained by equilibrium dialysis. The dissociation constants for the binding of both bilirubin and lithocholic acid were comparable with the various methods (range 0.2-0.7 microM). Thus, lithocholic acid and bilirubin share a high affinity binding site on gluthathione S-transferase B that appears to be separate from the binding site for substrates.